Building customer trust in cloud computing model - Pathan, Al-Sakib Khan (2015)
Building customer trust is a huge problem in the cloud computing paradigm. Today, hundreds of companies around the world are offering cloud services in major or minor scale with global or local reach. In spite of the availability of numerous establishments for cloud services, there is a critical link missing with the customers - and that is the lack of appropriate customer trust in the Cloud Provider’s (CP’s) services. The issue of trust in clouds has already been addressed from multiple technical perspectives where the researchers suggested solutions based on the existing knowledge in other computing and communications systems. After our investigation, we suggest a different concept of ensuring trust in cloud services by using the power of Information and Communications Technology (ICT). The basic idea lies in the fact that there should be a global standardization authority which would certify trusted cloud providers which in turn would earn customer trust. Novelty in this concept is mainly in its operational details that we have outlined. The main objective is to analyze various aspects of this proposed model from the policy making issues alongside slightly addressing technical issues. More issues about technicality and practicality can be addressed in future based on this initial framework.